PENGARUH KEPEMIMPINAN, KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN - Fauzi Rifqi Widoyo; Alfato Yusnar Kharismasyah; Herni Justiana Astuti; Fatmah Bagis (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to examine the influence of job satisfaction, leadership, and work environment on employee performance at Perumda Air Minum Tirta Perwira Purbalingga. The study is driven by the crucial role of human resources in ensuring the success of public service delivery, especially in the provision of clean water. Three independent variables, work environment, job satisfaction, and leadership, were analyzed against employee performance as the dependent variable. A quantitative method was utilized through survey techniques, with data collected via questionnaires. The sample consisted of 122 permanent employees with a minimum of one year of service, selected through purposive sampling. Data analysis utilized Partial Least Squares–Structural Equation Modeling (PLS-SEM) via the SmartPLS 4 software. The results indicate that all three independent variables, leadership, work environment, and job satisfaction significantly and positively affect employee performance. The study concludes that improving leadership quality, job satisfaction, and the workplace can function as successful approaches to enhance employee performance in public service institutions.